Mutations in six nephrosis genes delineate a pathogenic pathway amenable to treatment - Ashraf, Shazia; Kudo, Hiroki; Rao, Jia; Kikuchi, Atsuo; Widmeier, Eugen; Lawson, Jennifer A.; Tan, Weizhen; Hermle, Tobias; Warejko, Jillian K.; Shril, Shirlee; Airik, Merlin; Jobst-Schwan, Tilman; et al. (Nature Communications, 2018)
No efficient treatment exists for nephrotic syndrome (NS), a frequent cause of chronic kidney disease. Here we show mutations in six different genes (MAGI2, TNS2, DLC1, CDK20, ITSN1, ITSN2) as causing NS in 17 families with partially treatment-sensitive NS (pTSNS). These proteins interact and we delineate their roles in Rho-like small GTPase (RLSG) activity, and demonstrate deficiency for mutants of pTSNS patients. We find that CDK20 regulates DLC1. Knockdown of MAGI2, DLC1, or CDK20 in cultured podocytes reduces migration rate. Treatment with dexamethasone abolishes RhoA activation by knockdown of DLC1 or CDK20 indicating that steroid treatment in patients with pTSNS and mutations in these genes is mediated by this RLSG module. Furthermore, we discover ITSN1 and ITSN2 as podocytic guanine nucleotide exchange factors for Cdc42. We generate Itsn2-L knockout mice that recapitulate the mild NS phenotype. We, thus, define a functional network of RhoA regulation, thereby revealing potential therapeutic targets.
Created from Fastlane, Scopus look-up